Root Growth and Productivity of Wheat, Chickpea and Potato as Influenced by Nutrient Management Practices - Prajapat, Kailash; Vyas, A. K.; Dhar, Shiva (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during rabi / winter (November–March) seasons of 2011-12 and 2012-13 at research farm of Indian Agricultural Research Institute, New Delhi to evaluate the root growth and performance of wheat, chickpea and potato grown in different soybean-based cropping systems with 5 nutrient management practices. The results revealed that root growth in terms of root length, root volume and root dry weight of wheat and chickpea were observed significantly maximum where 50% RDN was substituted with FYM along with 50% RDF. Whereas, all the root parameters of potato were higher with the fertilization of 100% RDF. All the yield parameters and yields of wheat in soybean-wheat-fallow and soybean-wheat-mungbean cropping system did not differ significantly. All the yield parameters viz., effective tillers m-2, length of spike-1, grains spike and 1000-grain weight as well grain and stover yields of wheat were highest with the application of 100% RDF during both the years. Similarly, the maximum values of yield attributes and tuber and haulms yields of potato were recorded with the 100% RDF during both the years. However, no significant variation among all sources of nutrient was noticed during 2011-12 and among 100% RDF and substitution of 50% RDN through FYM during 2012-13 in both the crops. Whereas, significantly maximum yield contributing parameters and grain and stover yields of chickpea were found in the treatment receiving 50% RDF+50% RDN through FYM followed by 25% RDF+50% RDN through FYM+ biofertilizers during both the years.